TINDAK PIDANA PEMBUNUHAN YANG DISELESAIKAN SECARA ADAT YANG TIDAK SESUAI DENGAN PERUNDANG-UNDANGAN (KUHP DAN KUHAP) (Study kasus Desa Ture dan Desa Lubuk Ruso Kecamatan Pemayung di Kabupaten Batang Hari) - Fuad M. Yusuf (Universitas Batanghari Jambi, 2009)
The objective of this research is to give an alternative approach that can be used to account for murder crimes in accordance with the legal formal criminal code and material criminal code. This research was conducted in Batanghari Regency (Ture Village and Lubuk Ruso Village). This is a descriptive research that describes the rolr of adapt law in settling a murder case in relation with National Criminal code renewal.Police investigation must not be discontinued dispite that adapt law has settled the case. Chapter 102 article (1) of Act No.8 of 1981 says that an investigator who has knowledge, receive a report of a crime act must immediately conduct a necessary investigation. Further more, chapter 106 of the same act also says the same thing. In addition to this, chapter 14 article (1) letter g of act No.2 of 2002 on Police of The Republic of Indonesia Stipulates that the police of the Republic of Indonesia have the duty of conducting an investigation and research of any kinds of criminal code and other legislation.